EVALUASI HASIL PROYEK SMPFA DALAM MENINGKATKAN KUALITAS PELAYANAN KB PADA ASPEK PEMBERIAN INFORMASI DI PROVINSI JAWA TENGAH DAN JAWA TIMUR - , DRS. BAMBANG WIJONARKO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In cooperation with World Bank, the Indonesia government implemented safe motherhood project using family and partnership approach (Safe Motherhood project: a Partnership and Family Approach/SMPFA). Project intervention has been successful in increasing family planning service quality performance, especially in aspect of information provision (Subiyatun, 2002